2021
DOI: 10.5935/1984-0063.20200098
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing from preschool to early adult age and its neurocognitive complications: A preliminary report

Abstract: Objective:The onset and development of sleep disordered breathing (SDB) remains unclear in an age -dependent manner. Despite treatment, persistent symptoms such as snoring and excessive daytime sleepiness, as well as cognitive impairment may be present. The aim of the research was to determine the prevalence of residual symptoms of SDB in adolescence and early adulthood, the predisposing factors and its neurocognitive complications. Methods: In the present pilot studycohort, a questionnaire was utilized to 154… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Although snoring constitutes the major clinical symptom of OSAS both in adults and in children, it may not accompany pediatric OSAS in about 11% to 45% of patients. 1,23 We also observed that the sleep spindle activity did not show significant differences in children with OSAS with and without snoring. It seems that further data are needed to delineate whether primary snoring is a normal variant without significant clinical correlations or disease with hazardous consequences, for which further studies with larger study samples are needed.…”
Section: Discussionmentioning
confidence: 55%
“…Although snoring constitutes the major clinical symptom of OSAS both in adults and in children, it may not accompany pediatric OSAS in about 11% to 45% of patients. 1,23 We also observed that the sleep spindle activity did not show significant differences in children with OSAS with and without snoring. It seems that further data are needed to delineate whether primary snoring is a normal variant without significant clinical correlations or disease with hazardous consequences, for which further studies with larger study samples are needed.…”
Section: Discussionmentioning
confidence: 55%
“…. 30 Sleep deprived athletes are prone to both injuries and affected perceptual ability with slower reaction times. .…”
Section: Discussionmentioning
confidence: 99%
“…A sleep-deprived brain fails to recuperate neurons, undermining cognitive performance. General cognitive assessment tests unveil the cognitive phenotype of SD, especially in attention and short-term memory, as they anatomically overlap [ 36 , 37 ]. Furthermore, SD, in the context of sleep apnea, affects learning and memory [ 38 , 39 ] ( Table 1 ).…”
Section: Sleep Deprivationmentioning
confidence: 99%